Research on high-temperature graphitization of anthracite using Raman and electron paramagnetic resonance spectroscopy - Saik, Pavlo; Sybir, Artem; Vorona, Igor; Isaieva, Oksana; Yukhymchuk, Volodymyr; Trachevsky, Volodymyr; Burchak, Oleksandr; Hubynskyi, Ivan; Lozynskyi, Vasyl (Frontiers in Earth Science, 2025)
IntroductionThe high-temperature graphitization of anthracite is a key process for producing artificial graphite with properties comparable to natural graphite. However, the kinetics and structural evolution of carbon materials under rapid heating conditions remain insufficiently studied.MethodsThis study investigates the structural transformations of anthracite during staged heat treatment using Raman and electron paramagnetic resonance (EPR) spectroscopy. The experiments were conducted in an electrothermal fluidized bed system, providing heating rates up to 1000 K/min and holding times of several tens of minutes.ResultsThe combined analysis of Raman and EPR data revealed that graphitization occurs in three distinct temperature intervals. At 2,100°C, the product resembles natural graphite but retains a higher density of structural defects. At elevated temperatures of 2,700°C and 3,000°C, turbostratic graphite with fewer defects was obtained.DiscussionRapid heating and short annealing time facilitate the transformation of the two-dimensional carbon matrix into a more ordered three-dimensional structure while promoting the removal of ash-forming elements. Process optimization in terms of temperature and residence time is crucial for improving the structural integrity and performance of artificial graphite materials.